Nonenzymatic electrochemical detection of rutin on Pt nanoparticles/graphene nanocomposite modified glassy carbon electrode. Issue 27 (23rd June 2016) - Li, Shumin; Yang, Beibei; Wang, Jin; Bin, Duan; Wang, Caiqin; Zhang, Ke; Du, Yukou
Abstract : In this article, a nonenzymatic electrochemical sensor based on chemically reduced graphene oxide (RGO) and a Pt nanoparticles (PtNPs) modified glassy carbon electrode has been fabricated and used to determine rutin. Abstract : In this article, a nonenzymatic electrochemical sensor based on chemically reduced graphene oxide (RGO) and a Pt nanoparticles (PtNPs) modified glassy carbon electrode has been fabricated and used to determine rutin. The nanocomposites of PtNPs/RGO were characterized by transmission electron microscopy and X-ray diffraction, and the electrochemical behaviors of rutin on PtNPs/RGO were demonstrated by cyclic voltammetry and differential pulse voltammetry. The as-fabricated electrochemical sensor for rutin exhibited a wide linear range from 0.057 to 102.59 μM with a detection limit of 0.02 μM (S/N = 3). Additionally, the as-prepared electrode displayed a good reproducibility, stability and anti-interference ability for the detection of rutin. Finally, the electrode was successfully applied for the determination of rutin in pharmaceutical tablets.